Le procès Bruno Dey, un nouveau procès à la cage de verre - Bérénice Zunino (Criminocorpus)
This contribution seeks to analyse the media coverage of Bruno Dey's trial in BILD and in the taz, paying particular attention to press images. At the age of 93, Dey was charged with complicity in the murder of more than 5,230 people, at the Stutthof camp, in Poland, in 1944-1945. His trial was held in 2019-2020 in Hamburg, in the midst of the pandemic, requiring the installation of a plexiglass cage similar to that used in the trial of Eichmann (1961). The starting hypothesis of this article concerns the possible parallels with the media treatment of the Jerusalem trial. Indeed, at first glance, this parallel is daring: the trial of a theoretician of the “Final Solution” and that of a nonagenarian former camp guard seem to have very little in common. However, the work released by the photographers and journalists who covered the Dey trial suggests ‘games of variations’ in the treatment of Eichmann's images. Like a kaleidoscope, the images of Dey, monster and ordinary man at the same time, fit into multiple iconographic traditions in terms of media representations of Nazi criminals. Whether narrative, satirical or documentary, the images produced by the two press organs seek either the truth or the scandal. Despite the variety of messages, this media coverage of one of the last trials of Nazi criminals reveals the extent to which the memory of the Nazi past remains strongly present within German society.